Innovative antifungal strategies to combat drug-resistant Candida auris: recent advances and clinical implications - Du, Wei; Wang, Qihui; Zhao, Min (Frontiers in Cellular and Infection Microbiology, 2025)
Candida auris is an invasive fungal pathogen recognized globally as a significant health threat due to its marked resistance to multiple classes of antifungal agents, including azoles, echinocandins, and polyenes. The associated high morbidity and mortality rates present considerable public health challenges. Research efforts have largely focused on understanding the molecular mechanisms of antifungal resistance and developing alternative therapies to counteract this issue. This review summarizes current advances in the identification of natural antifungal compounds, the development of novel synthetic agents, biological antifungals, nanotechnology-based approaches, combination therapies, and photodynamic treatments. Notably, several synthetic compounds such as rezafungin and fosmanogepix are in clinical trials for C. auris infections. Biological antifungals, including monoclonal antibodies, vaccines, and peptides, have shown the capacity to enhance host immune responses and reduce mortality in murine models. Combination therapies have proven particularly valuable for overcoming resistance by exploiting synergistic effects and broadening antimicrobial coverage. Despite these promising developments, majority of studies have been conducted in vitro, with a relative lack of in vivo or human research. Therefore, further investigation is needed to validate the efficacy and safety of these alternative antifungal strategies for the treatment of drug-resistant C. auris infections.